The impact of globalization to creative industries: the analysis of film industries of Central and Eastern Europe - Mitkus, Tomas; Nedzinskaitė-Mitkė, Vaida (Creativity Studies, 2016)
This paper explores changes of the political, legal, taxation and other circumstances in film industries of Central and Eastern Europe that kick-started qualitative changes over the last decade. Research conducted by European Union (EU) on European film industry suggests that in terms of film industry Central and Eastern Europe region at this stage is generally non-competitive and not commercially orientated. We argue that the region filmmakers systematic believe in concept that film art and film business is a combination of polar opposites is a key reason that holds back industry’s potential to make a considerable economical and cultural contribution to national prosperity.First published online: 18 Dec 2015